Beneficial interaction of allelopathic bacteria with chemical herbicides for sustainable wheat (Triticum aestivum L.) production under wild oat (Avena fatua L.) infestation - Jaffar, Muhammad Tauseef; Zahir, Zahir Ahmad; Zhang, Jianguo; Dar, Abubakar; Ayyub, Muhaimen; Asghar, Hafiz Naeem (Italian Journal of Agronomy, 2023)
Weeds are one of the major limiting factors for wheat production. So, a study was conducted to integrate allelopathic bacteria with a reduced dose of chemical herbicide for sustainable wheat production in wild oat infestation. Cyanide-producing Pseudomonas strains were applied in 4 combinations with and without 2 chemical herbicides (Axial and Atlantis) at the 25% and 50% recommended doses under axenic conditions. Results showed that the C4 bacterial combination (combination of B11×T19×T24×T75 bacterial strains) significantly reduced the growth and development of wild oat under 50% Axial while increasing wheat growth. Subsequently, C4 combination and Axial herbicide were selected for field evaluation, where they reduced the weed density (82.1%), soil plant analysis development (SPAD) value (26.0%), grain yield (88.2%) under 75% Axial, relative wild oat density (70.9%), photosynthetic rate (26.6%), and transpiration rate (25.6%) under 50% Axial in wild oat. While the C4 combination improved SPAD value (26.9%), shoot length (10.1%), tillering (33.3%), biological yield (32.7%), straw yield (24.4%), grain yield (46.8%), transpiration rate (9.6%), and stomatal conductance (14.7%) in wheat under 75% Axial. The increase in growth and yield of wheat was found to be similar to C4 under 50% and 75% Axial. Thus, it is concluded that allelopathic bacteria could be used with 50% Axial for sustainable wheat production under wild oat.